INTEROPERATION OF LANGUAGE, SCIENTIFIC TERMINOLOGY, AND INTERDISCIPLINARY COLLABORATION - Madina Dalieva (Western European Studies, 2024)
This article delves into the dynamic interplay of language, science, and terminology, emphasizing the pivotal role of standardized terminology in fostering global scientific communication. Examining the evolution of scientific terminology, the study underscores its significance in preventing misunderstandings, enabling interdisciplinary collaboration, and reflecting the ever-changing landscape of scientific knowledge. Challenges in terminology creation, particularly in interdisciplinary contexts, are explored, highlighting the need for nuanced approaches to enhance cohesion across diverse scientific domains. Through case studies and critical analysis, the article contributes valuable insights to the ongoing discourse on the intricate relationship between terminology, language, and scientific communication.
Keywords: scientific terminology; language and science; interdisciplinary collaboration